Students' perceptions and experiences of a new "Teaching in Medicine" BMSc intercalated degree programme. (May 2014) - Muir, Fiona; Law, Susan
Abstract Objectives: Most doctors are involved in teaching to a greater or lesser degree and as such are required to keep their skills and knowledge up to date. Education for medical students has been moving up the political and professional agenda (GMC 2009, 2013). Currently, few Medical Schools offer a medical education intercalated degree programme. This study sets out to explore the students' experiences of a BMSc Teaching in Medicine Intercalated degree programme, offered by the School of Medicine Dundee, to help inform the value of an educational programme within an undergraduate medical curriculum. Methods: A small scale, exploratory case study was conducted with students who have completed the BMSc Teaching in Medicine Intercalated degree programme. A qualitative approach using three focus group interviews and questionnaire was carried out with 13 students within one University. Results: The results show the value of the programme and the merit of experiential learning gained throughout the programme. Students enhanced their learning through collaboration and opportunities gained within and out with the Medical School gaining a better appreciation of the roles and responsibilities of staff roles and academic clinicians. Conclusion: The findings highlight the value of an intercalated teaching degree within a MBChB programme, its application and relevance to future practice and career development, for continuing personal and professional development and lifelong learning.